2019
DOI: 10.1140/epjc/s10052-019-7400-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantum gravity effect on the Hawking radiation of spinning dilaton black hole

Abstract: The quantum gravity correction to the Hawking temperature of the 2+1 dimensional spinning dilaton black hole is studied by using the Hamilton-Jacobi approach in the context of the Generalized Uncertainty Principle (GUP). It is observed that the modified Hawking temperature of the black hole depends on both black hole and the tunnelling particle properties. Moreover, it is observed that the mass and the angular momentum of the scalar particle have the same effect on the Hawking temperature of the black hole, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Moreover, according to Equation ( 19), we can say that the standard Hawking temperature is higher than the modified Hawking temperature. In that case, the mass and angular momentum of the tunneling scalar particle play an important role in determining the thermodynamic properties of the wormhole, as in scalar particle tunneling from both 2 + 1and 3 + 1-dimensional black holes in the presence of the GUP effect [49,52,54,55,63,[65][66][67][68].…”
Section: Hawking Temperature Of the 2 + 1 -Dimensional Traversable Wormholementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, according to Equation ( 19), we can say that the standard Hawking temperature is higher than the modified Hawking temperature. In that case, the mass and angular momentum of the tunneling scalar particle play an important role in determining the thermodynamic properties of the wormhole, as in scalar particle tunneling from both 2 + 1and 3 + 1-dimensional black holes in the presence of the GUP effect [49,52,54,55,63,[65][66][67][68].…”
Section: Hawking Temperature Of the 2 + 1 -Dimensional Traversable Wormholementioning
confidence: 99%
“…On the other hand, when the thermodynamic properties of a black hole are examined in the context of the GUP which is based on the existence of a minimal observable length that is a characteristic of the candidate theories of quantum gravity, it is seen that the modified Hawking temperature is up to the properties of both the black hole and the tunneled particle . Furthermore, in the presence of the GUP effect, it was observed that the particles with spin (spin-0, 1/2, and 1) are differently tunneled from a black hole, and therefore, they caused completely different Hawking temperatures [63][64][65][66][67][68]. However, while the black hole thermodynamic is intensively studied in the literature, there are few studies that deal with thermodynamic properties of wormholes [69][70][71][72][73][74][75][76][77][78].…”
Section: Introductionmentioning
confidence: 99%
“…A question naturally arises: do quantum gravity corrections to the thermodynamic response functions depend on the particle's species? An answer has been sought for spin 0, spin 1/2, and spin 1 particles in different dimensional space-time backgrounds [32][33][34][35][36][37][38][39], and is still under investigation as in this present paper. At this stage, it is important to emphasize that the Unruh effect which is necessary for the internal consistency of the Quantum Field Theory (QFT) is being investigated in the context of GUP in addition to the Hawking radiation [40][41][42].…”
mentioning
confidence: 94%
“…That is to say, the H-J equation can uniformly describe the dynamic behavior of arbitrary spin fermions in the curved spacetime. Chen, Gecim et al studied the effects of quantum gravity on black holes utilizing the semi-classical H-J method and introducing the generalized uncertainty principle (GUP) [22][23][24][25][26][27][28][29][30][31][32]. Through this semi-classical H-J method, the calculation process was simplified, and so the amount of calculations was greatly reduced.…”
Section: Introductionmentioning
confidence: 99%